Multiple giant pilar cysts of scalp: A case report - Chowdhury, A Allam; Salam, Kazi Shameemus; Sultana, Tuhin; Amin, AS Ahmed; Datta, Pran Gopal (Bangladesh Journal of Otorhinolaryngology, 2011)
A rare case of multiple giant pilar cysts on scalp. Negligency by patients, delay in treatment causing enormous size of cysts. Local excision is the modality of treatment. Malignant transformation is rare. Key words: Pilar; trichilemmal cyst; Tumour DOI: 10.3329/bjo.v16i2.6849 Bangladesh J Otorhinolaryngol 2010; 16(2): 131-135